2010
DOI: 10.1103/physrevlett.105.048301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Desorption of Chlorobenzene Molecules from theSi(111)(7×7)Surface by Charge Injection from the Tip of a Scanning Tunneling Microscope: Remote Control o

Abstract: We report the nonlocal desorption of chlorobenzene molecules from the Si(111)-(7×7) surface by charge injection from the laterally distant tip of a scanning tunneling microscope and demonstrate remote control of the manipulation process by precise selection of the atomic site for injection. Nonlocal desorption decays exponentially as a function of radial distance (decay length ∼100  A) from the injection site. Electron injection at corner-hole and faulted middle adatoms sites couples preferentially to the deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 29 publications
5
63
0
Order By: Relevance
“…8 Additionally, the tautomerization behavior has been controlled by modifying the local surroundings of a molecule by using atom/molecule manipulation with an 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 STM. 4 Adsorbate reactions can be induced by the STM not only directly under the tip, but also at lateral distances from it (up to ~100 nm in an extreme case), 6,9,10,11,12,13,14,15,16 allowing remote control of adsorbate reactions. For such non-local reactions, the transport of hot carriers or the effect of an electric field has been proposed as a possible mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, the tautomerization behavior has been controlled by modifying the local surroundings of a molecule by using atom/molecule manipulation with an 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 STM. 4 Adsorbate reactions can be induced by the STM not only directly under the tip, but also at lateral distances from it (up to ~100 nm in an extreme case), 6,9,10,11,12,13,14,15,16 allowing remote control of adsorbate reactions. For such non-local reactions, the transport of hot carriers or the effect of an electric field has been proposed as a possible mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlocal activation of molecules has been observed in several systems 1-6 and is believed to result from (i) the electric field; 1 (ii) from hot electrons propagating through a surface, 2 organic thin film, 3 or self-assembled molecular chain; 4 or (iii) from mixing the molecular orbitals with the metal surface states. 5 The processes associated with ice nanocluster diffusion and hydrogen bond rearrangement in clusters on Au(111) 7 or the desorption of chlorobenzene from Si(111) 8 can be activated nonlocally by means of electron tunneling. Selective control over diffusion or desorption has been achieved by varying the distance between a molecule of interest 7 and an injection site.…”
Section: Introductionmentioning
confidence: 99%
“…Selective control over diffusion or desorption has been achieved by varying the distance between a molecule of interest 7 and an injection site. 8 Nonlocal activation is of particular interest in the field of nanoelectronics because charge transfer between adsorbed molecules and a surface determines the efficiency of a molecular electronic device 9 or the output of a hot carrier-induced solar cell. 10 Charge carriers, which are primarily injected using a scanning tunneling microscope (STM) tip, may be transferred to a reaction site directly or indirectly through surface states over long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Hot carriers that are injected from an STM tip can travel laterally in the surface state to the molecule and induce reactions in a spatially extended area around the tip location. In this context, it has been shown that molecules can be dissociated in a certain radius around the tip, which however is an irreversible process [14][15][16][17] . For actual devices reversible processes are much more relevant.…”
mentioning
confidence: 99%